2009
DOI: 10.1371/journal.pone.0008489
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation Results in Human Donor Blood Cells Acquiring and Displaying Mouse Recipient Class I MHC and CD45 Antigens on Their Surface

Abstract: BackgroundMouse models of human disease are invaluable for determining the differentiation ability and functional capacity of stem cells. The best example is bone marrow transplants for studies of hematopoietic stem cells. For organ studies, the interpretation of the data can be difficult as transdifferentiation, cell fusion or surface antigen transfer (trogocytosis) can be misinterpreted as differentiation. These events have not been investigated in hematopoietic stem cell transplant models.Methodology/Princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…(2016) 64:299-310 307 (Nygren et al 2004), kidney (Bonde et al 2010 and VCA (Ajiki et al 2005) transplantation. The survival and impact of DRCC is unknown (Kashofer et al 2006) and these cells may simply result either from in vivo cell fusion or from the transfer of plasma membrane fragments (trogocytosis) (Yamanaka et al 2009). Trogocytosis is the mechanism when large amounts of surface proteins can be transferred between the cells.…”
Section: Discussionmentioning
confidence: 99%
“…(2016) 64:299-310 307 (Nygren et al 2004), kidney (Bonde et al 2010 and VCA (Ajiki et al 2005) transplantation. The survival and impact of DRCC is unknown (Kashofer et al 2006) and these cells may simply result either from in vivo cell fusion or from the transfer of plasma membrane fragments (trogocytosis) (Yamanaka et al 2009). Trogocytosis is the mechanism when large amounts of surface proteins can be transferred between the cells.…”
Section: Discussionmentioning
confidence: 99%
“…1C,D), distinguishing cells co-expressing donor-host markers from doublets. To exclude ambiguity from surface antigen or membrane transfer between donor and host hematopoietic cells (Yamanaka et al, 2009) Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…S2). This is probably due to cell membrane sharing (trogocytosis) between cells (Yamanaka et al, 2009). As evident from the decreased frequency of fusion events subsequently validated by genetic assays, FACS is suitable for the prospective recovery, but suffers from lower specificity.…”
Section: Frequency Of Hematopoietic Cell Fusion Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, the authors observed the presence of mouse MHC class I protein on the surface of almost all human cells, suggesting that this mechanism was adopted by the human cells to evade host immune surveillance [ 60 ]. Follow up study by Chow T et al showed that transfer of MHC Class I from host to the donor cells plays an important role in protecting donor cells from NK cell and macrophage mediated rejection during hematopoietic stem cell transplantation and engraftment [ 61 ].…”
Section: Mechanism Of Chimeric Cell Creation In Vivomentioning
confidence: 99%